Implementasi Tahfizh Al-Qur’an dalam Meningkatkan Sikap Relegius Siswa di MTs Jamiat Kheir Tanah Abang Jakarta Pusat - Hendrayadi, Hendrayadi; Nurhayati, Eneng (LP2M, Institut Agama Islam Qamarul Huda, 2025)
This study aims to analyze the implementation of the Al-Qur'an memorization program and its impact on students' religious attitudes at MTs Jamiat Kheir Tanah Abang. This study used a descriptive qualitative approach with observation, interview, and documentation techniques. The results showed that the memorization program had a positive impact on improving students' discipline, spiritual awareness, and morals. However, time constraints and consistency in memorization were the main obstacles. This study recommends innovation in memorization methods and parental involvement in supporting memorization at home.